2013
DOI: 10.1292/jvms.12-0442
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hantavirus Infection in Thousand Islands Regency of Jakarta, Indonesia

Abstract: ABSTRACT. Hemorrhagic fever with renal syndrome (HFRS) is a rodent-borne zoonotic disease caused by hantavirus infection. Many HFRS cases have been reported in East Asia and North Europe, while the situation in Southeast Asia remains unclear. In this study, the prevalence of hantavirus infection in rodents and humans in Thousand Islands regency, which is close to the port of Jakarta, one of the largest historic ports in Indonesia, was investigated. A total of 170 rodents were captured in 2005, and 27 (15.9%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…However, the seroprevalence and infection of hantavirus in rodent and human populations of East Malaysia are still largely unknown. There were also several reported cases of rodents infected with hantavirus in neighbouring countries [i.e., China (Lin et al 2012;Wang et al 2000), South Korea (Lim et al 2012), Singapore (Wong et al 1985(Wong et al ,1988Johannson et al 2010), Indonesia (Plyusnina et al 2009;Ibrahim et al 2013), Thailand, Cambodia and Lao PDR (Nitatpattana et al 2000;Reynes et al 2003;Blasdell et al 2011Blasdell et al , 2016], which suggested that there was a possibility for the circulation of hantavirus in the rodent populations in East Malaysia.…”
mentioning
confidence: 99%
“…However, the seroprevalence and infection of hantavirus in rodent and human populations of East Malaysia are still largely unknown. There were also several reported cases of rodents infected with hantavirus in neighbouring countries [i.e., China (Lin et al 2012;Wang et al 2000), South Korea (Lim et al 2012), Singapore (Wong et al 1985(Wong et al ,1988Johannson et al 2010), Indonesia (Plyusnina et al 2009;Ibrahim et al 2013), Thailand, Cambodia and Lao PDR (Nitatpattana et al 2000;Reynes et al 2003;Blasdell et al 2011Blasdell et al , 2016], which suggested that there was a possibility for the circulation of hantavirus in the rodent populations in East Malaysia.…”
mentioning
confidence: 99%
“…However, the result of study in Indonesia revealed various results. The percentage of positive hantavirus infection on R. norvegicus was between 8.2% to 44.7% [5,14,15]. Higher percentage of hantavirus infection on R. norvegicus in the study site showed that the site had a high risk for Hantavirus transmission.…”
Section: Discussionmentioning
confidence: 82%
“…Rats are the main reservoir host of hantavirus and leptospirosis infection [3][4][5]. The transmission of hantavirus infection and leptospirosis is related to one's exposure with the rats and its feces [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SEOV strains are found in ports and countries with overseas traffic, no SEOV infections of rats or humans have been reported in Sulawesi in Indonesia. SEOV RNA in rats, but no proof of human infections, was reported in Jakarta, on the island of Java in Indonesia ( 10 , 11 ). …”
Section: Discussionmentioning
confidence: 99%